Are Halide‐Perovskites Suitable Materials for Battery and Solar‐Battery Applications–Fundamental Reconsiderations on Solubility, Lithium Intercalation, and Photo‐Corrosion. (3rd October 2022) - Büttner, Jan; Berestok, Taisiia; Burger, Stephan; Schmitt, Manuel; Daub, Michael; Hillebrecht, Harald; Krossing, Ingo; Fischer, Anna
Abstract: In recent years the development of autonomous photo‐rechargeable batteries has received growing attention. Especially highly integrated photobatteries based on multifunctional materials able to harvest sunlight and store charge carriers are the holy grail amongst such devices. Recently 2‐(1‐cyclohexenyl)ethyl ammonium lead iodide (CHPI) has been reported as multifunctional photoelectrode material for the design of highly integrated Li‐ion photobatteries. CHPI is thereby believed to be able to reversibly intercalate Li‐ions from polar carbonate‐based electrolytes, typically used in Li‐ion batteries (LIBs). Herein, CHPI is examined closer to investigate its stability against dissolution, the possibility of Li‐intercalation and photo‐assisted deintercalation, and its general behavior under illumination in standard carbonate‐based electrolytes as well as in a newly developed low polarity electrolyte based on ortho ‐difluorobenzene ( o ‐DFB). This study demonstrates that CHPI dissolves in contact with carbonate‐based electrolytes while being stable in o ‐DFB‐based electrolyte and that no Li‐intercalation takes place in the latter. Furthermore, CHPI irreversibly photo‐corrodes during illumination and photo‐assisted deintercalation of lithium ions is not detected. These results lead to the conclusion, that CHPI is neither a suitable nor a stable material for the design of Li‐ion‐based photo‐rechargeable batteries and similar behavior for other organic–inorganic lead halide perovskite materials is expected. Abstract : 2‐(1‐cyclohexenyl)ethyl ammonium lead iodide (CHPI) is investigated towards its applicability in a mode 3 photo‐battery. Therefore its stability against dissolution, possible Li‐intercalation in CHPI, photo‐assisted deintercalation and general behavior under illumination is studied. It is found that in contrast to existing literature CHPI is inherently chemically, electrochemically and photochemically instable when in contact with liquid electrolytes and shows no Li‐intercalation ability and is therefore unsuitable for any usage in a mode 3 photo battery.